Pengaruh Harga Promo Yang Di Berikan Terhadap Minat Beli Kamar Pada Hotel Bintang Lima Di Kota Palembang - Anggraini, Lili; Nathasya, Nurvia (Jurnal Kajian Pariwisata Dan Perhotelan, 2023)
The price of this hotel varies based on the type and facilities provided. The more luxurious the facilities provided, the more expensive the price given by the hotel. The purpose of this study is to determine the effect of promo prices given on the interest in buying rooms at five-star hotels in Palembang City. The sampling technique in this study uses the saturation technique, which is the determination of samples from the entire population that is too small, so that the sample in this study is 35 people. The technique used in this study is quantitative descriptive analysis using the help of SPPS 22.0 for Windows. The result of this study is that the promo price given by five-star hotels in the city of Palembang has a significant effect on the interest in buying rooms